Kevesebb tanuló, kevesebb iskola? : a kistelepülések kisiskoláit érintő változások - Herendi, István (Közép-Európai Közlemények, 2009)
The changes in the system of the public education in Hungary have permanently been part of a long development process. The responsibility of this system is mostly on local and county authorities. There is a new phenomena: more and more local authorities cooperate with other local ones to satisfy educational needs at a sons why cooperation come into life are on one hand the decrease of financial sources and on the other hand the relatively high costs caused by demographic trends. The present situation of schools seems to be critical in small villages and in a sig-This paper analyses some details on relatioship of small villages and small schools. The description is based on national and regional datarecords. It is extremly important to preserv traditional values of small villages. Besides strengthe role of centrum it is also important to keep the characteristics and interests of these villages. The role of small schools will be changed in the future. We must stress the values of traditions an the human factors in these areas.